2014
DOI: 10.3855/jidc.4204
|View full text |Cite
|
Sign up to set email alerts
|

Demographic distribution and transmission potential of influenza A and 2009 pandemic influenza A H1N1 in pilgrims

Abstract: Introduction: The World Health Organization's persistent reporting of global outbreaks of influenza A viruses, including the 2009 pandemic swine A H1N1 strain (H1N1pdm09), justified the targeted surveillance of pilgrims during their annual congregation that pools more than two million people from around 165 nations in a confined area of Makkah city in the Kingdom of Saudi Arabia (KSA). Methodology: A total of 1,600 pilgrims were included in the targeted surveillance of influenza A and the 2009 pandemic swine H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 31 publications
(40 reference statements)
2
26
0
Order By: Relevance
“…However, meta-analysis of the data from 6 studies which provided both laboratory results by vaccination status [10,14,16,22,25,33] shows that the influenza vaccine was significantly protective against laboratory-confirmed influenza among Hajj pilgrims (RR, 0.56; 95% CI, 0.41-0.75; p < 0.001) (Fig. 2).…”
Section: Influenza Vaccine Effectivenessmentioning
confidence: 93%
See 3 more Smart Citations
“…However, meta-analysis of the data from 6 studies which provided both laboratory results by vaccination status [10,14,16,22,25,33] shows that the influenza vaccine was significantly protective against laboratory-confirmed influenza among Hajj pilgrims (RR, 0.56; 95% CI, 0.41-0.75; p < 0.001) (Fig. 2).…”
Section: Influenza Vaccine Effectivenessmentioning
confidence: 93%
“…Of these, 6 studies reported laboratory-confirmed influenza as an outcome [10,14,16,22,25,33], but only one study found influenza vaccine to be effective in reducing influenza (p < 0.001) [10]. However, meta-analysis of the data from 6 studies which provided both laboratory results by vaccination status [10,14,16,22,25,33] shows that the influenza vaccine was significantly protective against laboratory-confirmed influenza among Hajj pilgrims (RR, 0.56; 95% CI, 0.41-0.75; p < 0.001) (Fig.…”
Section: Influenza Vaccine Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…Rhinoviruses,[345] coronaviruses (E229 – SARS – MERS),[6] adenoviruses, both seasonal and pandemic influenza[7] including, influenza A (H3N2) and B,[3] influenza H1N1, parainfluenza viruses, respiratory syncytial viruses, herpes simplex virus,[589] meningococcal diseases[10] and meningococcal carrier state,[11] emerging hypervirulent strains, i.e., Streptococcus spp.,[10] Haemophilus influenzae ,[3] Bordetella pertussis ,[12] Chlamydophila pneumoniae , Legionella pneumophila , Mycoplasma pneumonia ,[3] and respiratory tuberculosis. [13]…”
Section: Introductionmentioning
confidence: 99%